ANALISIS EFISIENSI USAHATANI PADI SAWAH: KASUS PADA PETANI PENGGUNA HANDTRAKTOR DI KELURAHAN KEMUMU, KECAMATAN ARGAMAKMUR, KABUPATEN BENGKULU UTARA - Tsaputra, Harry; Sumantri, Bambang; Purwoko, Agus (Jurnal AGRISEP, 2012)
The objective of this study is to analyze the efficiency and risk of rice farming with and without hand tractor. Sixty six respondents are selected using simple random sampling. R/C ratio is used to estimate farm efficiency and business risk analysis as suggested by Kadarsan (1995) is used to examine risk that is probably faced by farmers. The results showed that farmers used tractors is more efficient than others. This conclusion is based on average R/C ratio of 3.02 and 2.69 for farmers with and without tractor respectively. Statistic t test also support the existence of economic efficiency dissimilarity.